Do tourism revenues effects financial and real sector in Turkey - ÇAKMUR YILDIRTAN, ZEYNEP DİNA (My University, 2021)
indicators. For this reason, tourism revenues have great importance to reduce the current account deficit in fragile markets such as Turkey. For tourism revenues to increase, together with the location of the country the exchange rate in terms of local currency should be worthless against foreign currency. In other words, low exchange rate and geographical location increase tourism revenues. This study examines the relationship between the tourism sector, finance sector and real sector. For this purpose, total travel revenues, average travel expenditures per person, total travel expenses, CPI-based real effective exchange rate, PPI based real effective exchange rate, BIST100 closing index (BIST100) and manufacturing industry capacity utilization rate variables were analyzed. The variables included in the analysis cover the period 2007-2018 with monthly frequency. The main feature that distinguishes this study from other studies is to analyze the relationship between tourism revenues and macroeconomic variables, and to investigate the relationship between the stock market index and tourism revenues.

Türkiye gibi gelişmekte olan piyasalar için cari açık önemli kırılganlık göstergelerinden biri olarak karşımıza çıkmaktadır. Bu sebeple Türkiye gibi kırılgan piyasalarda cari açık miktarının düşürülebilmesi için turizm gelirleri büyük önem arz etmektedir. Turizm gelirlerinin artabilmesi için ülkenin bulunduğu konumla birlikte döviz kurunun yerel para cinsinden yabancı paraya karşı değersiz olması gerekmektedir. Bir diğer deyişle düşük kur ve coğrafi konum turizm gelirlerini artırmaktadır. Bu çalışma, turizm sektörü, finans sektörü ve reel sektör arasındaki ilişkiyi incelemektedir. Bu amaçla toplam seyahat gelirleri, kişi başı ortalama seyahat giderleri, toplam seyahat harcamaları, TÜFE bazlı reel efektif döviz kuru, ÜFE bazlı reel efektif döviz kuru, BIST100 kapanış endeksi ve imalat sanayi kapasite kullanım oranı değişkenleri analiz edilmiştir. Analize dahil edilen değişkenler aylık frekans ile 2007-2018 dönemini kapsamaktadır. Bu çalışmayı diğer çalışmalardan ayıran temel özellik turizm gelirlerinin makroekonomik değişkenler ile olan ilişkisini analiz etmekle birlikte borsa endeksi ile turizm gelirlerinin de ilişkisini araştırmaktadır.
Türkiye'de turizm gelirleri finans ve reel sektörü etkiler mi
Keywords: Tourism Revenues; Causality; Cointegration; Industrial Growth; Turizm Gelirleri; Nedensellik; Eşbütünleşme; Endüstriyel Büyüme